2007
DOI: 10.1016/j.jana.2007.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Health Care Providers and Appointment Attendance in HIV/AIDS Patients

Abstract: Patients with HIV/AIDS are likely to have numerous interactions with health care providers (HCPs) during the course of their disease. Research has shown that satisfaction with one's HCP is related to better medication adherence in patients with HIV/AIDS. Although a patient's attitude toward his or her HCP is important, little has been done to assess how it relates to appointment attendance. The current study assessed how attitudes toward HCPs as well as social support and depression relate to outpatient appoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 23 publications
5
41
0
Order By: Relevance
“…This study showed an association between social support and adherence among ADHC clients, as seen in other studies of PLWH (Bader et al, 2006;Bodenlos et al, 2007;Simoni et al, 2006). This study was not designed to establish causality, and the authors therefore cannot say that ADHC participation leads to increased social support or to increased adherence, or that increased social support leads to increased adherence in the ADHC setting.…”
Section: Limitations Of the Studysupporting
confidence: 65%
See 1 more Smart Citation
“…This study showed an association between social support and adherence among ADHC clients, as seen in other studies of PLWH (Bader et al, 2006;Bodenlos et al, 2007;Simoni et al, 2006). This study was not designed to establish causality, and the authors therefore cannot say that ADHC participation leads to increased social support or to increased adherence, or that increased social support leads to increased adherence in the ADHC setting.…”
Section: Limitations Of the Studysupporting
confidence: 65%
“…The high scores in reliable alliance could be interpreted as having the feeling of a safety net, reflecting the goals of ADHC care (Murphy et al, 1999). The difference in the social support subscale between the adherence groups was statistically significant (p 5 .02), suggesting an association between adherence and social support as has been observed in other groups of PLWH (Bader et al, 2006;Bodenlos et al, 2007;Simoni et al, 2006). Mean subscale scores were higher for instrumental provisions and lower for emotional provisions in both the adherent and nonadherent groups.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, discriminatory attitudes of society or HIV-related-care providers toward PLWHA may have a negative impact on adherence for treatment by people with symptoms of HIV (Brener, von Hippel, von Hippel, Resnick & Treloar 2010). Whereas, positive attitudes toward PLWHA have led to increase in adherence for treatment (Bodenlos et al 2007). Implementation of population-based programs through mass media for all people has to be taken into account as well.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with positive attitudes toward their healthcare provider were more likely to attend their healthcare appointments. 15 Whetten et al 16 interviewed 611 HIV-infected individuals to assess whether higher trust in healthcare providers and the government was related to better healthcare utilization in the past and better health outcomes at the time of interview. Higher trust in healthcare providers was associated with increased outpatient visits and reduced emergency room visits in the past 9 months; and increased likelihood of taking antiretroviral therapy, and improved mental and physical health at the time of the interview.…”
Section: Introductionmentioning
confidence: 99%